Etika Bisnis Dalam Islam - Ahmad Bisri Musthafa (STAI Al-Mas'udiyah, 2022)
Economic practices at the time of the Prophet and Khulafaurrasydin showed a large role of the market. The research method used is descriptive research is a form of research aimed at describing existing phenomena, both natural phenomena and man-made phenomena, can be in the form of forms, activities, characteristics, changes, relationships, similarities, and differences between one phenomenon and another. . This research data collection technique uses two kinds of data sources, namely primary data and secondary data. The results showed that the Prophet really appreciated the price set by the market as a fair price. However, the market here requires morality, including: fair competition, honesty, openness, and fairness. If these values ​​have been established, then there is no reason to reject the market price. so that in the market there is a sale and purchase called muamalah. Business ethics in Islam is not limited to mere study and research, but more than that business ethics in Islam needs to be applied in modern business practices. In the perspective of Islamic law, there are basic principles that must be avoided in doing business, namely: it does not contain elements of usury, does not contain elements of fraud and does not do business with prohibited goods.